2022
DOI: 10.1016/j.clbc.2021.12.009
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Molecular and Clinical Characteristics of Apocrine Carcinoma of the Breast

Abstract: Apocrine carcinoma of the breast is a rare malignancy. According to 2019 WHO classification, apocrine cellular features and a characteristic steroid receptor profile (Estrogen receptor (ER)-negative and androgen receptor (AR)-positive) define apocrine carcinoma. Her-2/neu protein expression is reported in ∼30-50% of apocrine carcinomas, while NGS analysis showed frequent PIK3CA/PTEN/AKT and TP53 mutations Followed by deregulation in the mitogen-activated protein kinase pathway components (mutations of KRAS, NR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
2
12
0
Order By: Relevance
“…Despite these differences, TNAC is treated in the same manner as other TNBC, although the benefit of the AR antagonist bicalutamide was investigated in advanced ER- and PR-negative patients [ 30 ]. In concordance with previous studies [ 31 , 32 , 33 , 34 ], our results demonstrate that apocrine carcinoma has better prognosis than invasive breast carcinoma of no special type. More significantly, our results showed that TNAC patients have a poor chemotherapy responsiveness and no benefit from chemotherapy in terms of BCSS.…”
Section: Discussionsupporting
confidence: 93%
“…Despite these differences, TNAC is treated in the same manner as other TNBC, although the benefit of the AR antagonist bicalutamide was investigated in advanced ER- and PR-negative patients [ 30 ]. In concordance with previous studies [ 31 , 32 , 33 , 34 ], our results demonstrate that apocrine carcinoma has better prognosis than invasive breast carcinoma of no special type. More significantly, our results showed that TNAC patients have a poor chemotherapy responsiveness and no benefit from chemotherapy in terms of BCSS.…”
Section: Discussionsupporting
confidence: 93%
“…We observed some clinically relevant differences between the APO and NST groups. Thus, HER2+/SR−/APO had significantly lower histological grade than the NST carcinomas, which is in line with several previous studies and is probably due to the lower mitotic activity (and lower Ki-67 labeling) of apocrine cells [ 9 , 17 , 19 , 20 ]. Lower tumor grade may also contribute to the less aggressive behavior of HER2+/APO, as confirmed in a large cohort of IBS NST in which a high histological grade was a strong predictor of an adverse outcome [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…APO is a rare (frequency ~ 1%) subtype of breast carcinoma whose diagnosis and clinical data, including outcome, remain challenging and controversial [ 14 , 19 ]. Based on the SEER data (2010–2016), the current study represents the largest HER2-positive APO cohort reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations